Engagement policies and practices: expanding the citizenship of the Brazilian diaspora - Padilla, B. (International Migration, 2011)
Immigration has certainly changed many aspects of politics and policies, and citizenship is one of them. Due to migration, both countries of origin and destination have been forced to look at citizenship with different eyes and both have gained interest in looking at migrants (both emigrants and immigrants) for different reasons. While countries of origin are designing engagement policies with the goal of strengthening ties to the diaspora, countries of destinations are designing integration and citizenship policies to relate to newcomers. However, immigrants find themselves in a complex situation, as they engage in dual practices which aim at expanding and securing their citizenship in both contexts. This paper examines the case of the Brazilian diaspora in Portugal, and explores the concept of transnational citizenship (from the countries of origin and destination, top-down and bottom-up citizenship, and contesting citizenship) including its use in generating political belonging, and its application in the specific context of bilateral relations between Brazil and Portugal.